Postmodernistični elementi v poeziji Jevrema Brkovića - Vučinić Gujić, Anka M. (Slavistična revija, 2016)
The semantic and stylistic heterogeneity of Jevrem Brković's poetic discourse does not lend itself to a single artistic paradigm. Instead, the amalgamation of traditional, modern, and postmodern layers help to build new textuality. The differentiation of poetic expressions resulting from the inability to comprehend the totality is reflected in the introduction of historiographical metafiction and intertextuality as inherent features of the poetics of postmodernism.
Keywords: Brković, Jevrem, 1933-; črnogorska književnost; črnogorska poezija; črnogorski pisatelji; intertekstualnost; Intertextuality; postmodernizem; semiotični pristop